2007
DOI: 10.1007/s10577-007-1158-6
|View full text |Cite
|
Sign up to set email alerts
|

Karyology, mitochondrial DNA and the phylogeny of Australian termites

Abstract: A comprehensive karyological characterization of 20 Australian and three European species of Isoptera, together with a mitochondrial gene analysis is presented. Higher termites appear karyotypically very uniform, while lower termites are highly variable. The differences in chromosome number are explained through Robertsonian changes or multiple translocation events. An ancestral acrocentric karyotype can be suggested as the most primitive one. In Kalotermitidae chromosomal repatterning has repeatedly arisen wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 53 publications
(70 reference statements)
0
20
1
Order By: Relevance
“…Studies of termite chromosomes showed that higher termites (Termitidae) have a fixed number of chromosomes (2n=42), while the diploid number of chromosomes in lower termites varies from 28 to 56 (Bergamaschi et al, 2007). Reticulitermes termites have 2n=42 chromosomes.…”
Section: Termite Parthenogenesismentioning
confidence: 99%
“…Studies of termite chromosomes showed that higher termites (Termitidae) have a fixed number of chromosomes (2n=42), while the diploid number of chromosomes in lower termites varies from 28 to 56 (Bergamaschi et al, 2007). Reticulitermes termites have 2n=42 chromosomes.…”
Section: Termite Parthenogenesismentioning
confidence: 99%
“…Parthenogenesis induced by endosymbiotic bacteria has only been confirmed in host taxa with haplo-diploid sex determination (in which males develop from unfertilized haploid eggs and females from fertilized eggs), although the strong overrepresentation of haplo-diploids among species with known endosymbiont-induced parthenogenesis may be due to an ascertainment bias [9]. Termites are diploid and typically have an XY sex determination system [11]. Notably, four of six examined termite species with facultative parthenogenesis do not appear to harbour endosymbiotic bacteria [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…Within Isoptera (termites), the more evolved, i.e. "higher" groups are karyologically uniform with 2n = 42, while "lower" termites are more variable, with 2n ranging from 28 to 56 (Bergamaschi et al, 2007). very little is known about the karyotypes of the small order Embio pte ra in which chromosome numbers lie between 19 and 23 (White, 1976;Hodson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%